Reliability and Validity Study of the Finnish Adaptation of Scoliosis Research Society Questionnaire Version SRS-30 - Kyrölä, Kati; Järvenpää, Salme; Ylinen, Jari; Mecklin, Jukka-Pekka; Repo, Jussi Petteri; Häkkinen, Arja (Spine (Philadelphia, Pa. 1976), 2017)
A prospective clinical study to test and adapt a Finnish version of the Scoliosis Research Society 30 (SRS-30) questionnaire. The aim of this study was to perform cross-cultural adaptation and evaluate the validity of the adapted Finnish version of the SRS-30 questionnaire. The SRS-30 questionnaire has proved to be a valid instrument in evaluating health-related quality of life (HRQoL) in adolescent and adult population with spine deformities in the United States. Multinational availability requires cross-cultural and linguistic adaptation and validation of the instrument. The SRS-30 was translated into Finnish using accepted methods for translation of quality-of-life questionnaires. A total of 274 adult patients with degenerative radiographic sagittal spinal disorder answered the questionnaire with sociodemographic data, RAND 36-item health survey questionnaire (RAND Corp. Health, Santa Monica, CA, US), Oswestry disability index, DEPS depression scale, and Visual Analog Scale (VAS) back and leg pain scales within 2 weeks' interval. The cohort included patients with and without previous spine surgery. Internal consistency and validity were tested with Cronbach α, intraclass correlation (ICC), standard error of measurement, and Spearman correlation coefficient with 95% confidence intervals (CIs). The internal consistency of SRS-30 was good in both surgery and nonsurgery groups, with Cronbach α 0.853 (95% CI, 0.670 to 0.960) and 0.885 (95% CI, 0.854 to 0.911), respectively. The test-retest reproducibility ICC of the SRS-30 total and subscore domains of patients with stable symptoms was 0.905 (95% CI, 0.870-0.930) and 0.904 (95% CI, 0.871-0.929), respectively. The questionnaire had discriminative validity in the pain, self-image, and satisfaction with management domains compared with other questionnaires. The SRS-30 questionnaire proved to be valid and applicable in evaluating HRQoL in Finnish adult spinal deformity patients. It has two domains related to deformity that are not covered by other generally used questionnaires. 3.